From efficiency-driven to innovation-driven economic growth : perspectives from Singapore - Tan, Kim Song (Policy research working paper, 2005)
"This paper looks at Singapore's efforts to transform the economic growth base from one that is predominantly efficiency-driven to one that is more innovation-driven. To accelerate the transition process, the government is aggressively investing in "innovation infrastructure"-systems and institutions that make the city a more conducive environment for innovations. The modus operandi, with a distinctive "winner-picking" flavor, mirrors that of its earlier strategic industrial policy in building up the manufacturing sector. It is also in sync with the new urban growth literature which argues that the success of any innovation-driven growth strategy depends on a city's ability to attract a large community of creative individuals in different fields. Innovation infrastructure building requires more than putting in the right systems. It also requires a mindset change at various levels of society. This paper looks at how the government's policy philosophy and practices have evolved over time, and discusses the effectiveness of the government-led, strategic supply-push approach in propelling Singapore onto an innovation-driven growth path. It takes into consideration the city-state's underlying comparative advantages (or disadvantages) and asks how Singapore's existing strength in efficiency infrastructure may give it a first mover advantage in attracting creative talent, how its success may be affected by the small size of the economy, and the various political and social constraints that a small sovereign city-state faces. These issues are explored against the backdrop of the keen competition among the major cities in the region to become an innovation hub. "--World Bank web site